2013
DOI: 10.1016/j.hlc.2013.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Pevalence of Pseudohypertension in a Contemporary Patient Cohort Undergoing Cardiac Catheterisation

Abstract: Background: Pseudohypertension refers to the phenomenon of indirect sphymanonometry to overestimate systolic blood pressure when compared to invasive measurement. This frequently complicates assessment in the elderly due to arterial calcification, which results in an inability to compress the artery during cuff inflation and has important clinical implications. The prevalence and predictors of pseudohypertension are poorly defined. Aims: We sought to evaluate the prevalence of pseudohypertension in a contempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a retrospective study (Kleman et al, 2013), conducted on patient attending a hypertension clinic, it was found that 7% of the patients had pseudohypertension [3]. In a parallel cohort study (Collins et al, 2013), the prevalence of systolic pseudohypertension in patients undergoing Cardiac Catheterization was detected in 10.8% of patients, and the majority were of advanced age [4]. In relation to the clinical examination of pseudohypertension, Osler's maneuver is to be performed for assessing the palpability of pulsation of the radial and/or brachial artery distal to a point of the suspected arterial pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study (Kleman et al, 2013), conducted on patient attending a hypertension clinic, it was found that 7% of the patients had pseudohypertension [3]. In a parallel cohort study (Collins et al, 2013), the prevalence of systolic pseudohypertension in patients undergoing Cardiac Catheterization was detected in 10.8% of patients, and the majority were of advanced age [4]. In relation to the clinical examination of pseudohypertension, Osler's maneuver is to be performed for assessing the palpability of pulsation of the radial and/or brachial artery distal to a point of the suspected arterial pathology.…”
Section: Introductionmentioning
confidence: 99%